The relationship of affective and cognitive-based trust, internal work motivation and job performance in higher learning institutions - Bouzidani, Ibrahim; Abdul Rahman, Shukran (2011)
This study investigated the relationship of affective and cognitive based trust among peers as a social characteristic of job design, with two work-related variables; internal work motivation as an attitudinal outcome of job design; and job performance as a behavioural outcome of job design. The participants were selected by employing systematic random sampling from the population of academic members in a higher learning institution. A total of 132 subjects (N = 132) participated in this study. Using structural equation modelling the results demonstrated that the affective based trust was not significantly related to either of the two outcomes variables; however, the cognitive based trust was found to have a significant relationship with job performance.